The determination of the nursing students prevalance of cigarette smoking and affecting factors - Koç, Z.; Sağlam , Z. (Journal of Dependence, 2008)
Introduction: This is a descriptive study designed to investigate the prevalence of smoking among nursing students, the factors affecting smoking, the reasons for current smoking, and their approaches to quitting and not smoking. Method: The study was conducted on 128 nursing students, and data were collected using a 28-question survey in March 2005. Findings: The prevalence of smoking was found to be 28.1%. One in four nursing students included in the study was found to be a smoker. It was determined that 88% of non-smoking nursing students did not smoke for health reasons. It was determined that nursing students continued to smoke due to stress (63.9%). The educational level of the nursing students' mothers and fathers was associated with an increase in smoking prevalence (p
Keywords: cigarette